The Adoption of e‐Commerce in the Lesotho Tourism Industry. Issue 1 (5th December 2017) - Mapeshoane, Tsebetso J.; Pather, Shaun
Abstract: Over the years, Information and Communication Technology (ICT) has been revolutionising global markets. In developed nations, for example, there has been a push for developing countries to adopt ICT as leverage towards improving their economic development. However, in the current era, ICT adoption has not been as widespread as anticipated in some parts of the world, with its use in developing countries especially, lagging behind. This is particularly so amongst the small, medium, micro‐enterprise (SMME) sector, important drivers of the economy in the developing world. SMMEs in developing countries have been hindered in the uptake of ICTs, largely due to underlying issues such as the high cost of ICT, inadequate and unreliable infrastructure, as well as lack of policy necessary to promote competition and growth within the ICT sectors. Amongst varying applications of ICTs, e‐commerce is one area in particular which SMMEs have been relatively reluctant to adopt. Presently, many African countries have already taken firm steps to address infrastructure and ICT access issues. However, improved access on its own will not result in economic growth. It is important, therefore, to also understand aspects of ICT adoption in developing countries. The purpose of this research was to investigate the factors affecting e‐commerce adoption in a typical developing country. Lesotho presented itself as an ideal case to investigate e‐commerce adoption amongst SMMEs, specifically within the Lesotho tourism industry. This study, then, provides a detailed explanation of the factors influencing e‐commerce uptake in the Lesotho tourism sector. In the extant literature, several studies and a number of generic models and frameworks on technology adoption offer a generalised understanding of technology adoption. None of these, however, provide a contextualised perspective prevalent to businesses in the typical developing country environment. Evidence for the study was collected using interviews with businesses. Data collected via interviews was used to examine the actual adoption issues amongst tourism SMMEs in Lesotho. In addition, where applicable, each organisation's online activities or websites was assessed. The study was premised on the Unified Theory of Acceptance and Use of Technology (UTAUT) model as its framework. The findings revealed that dimensions of the UTAUT model provided a sensible explanation regarding behavioural intention to adopt and use e‐commerce amongst tourism SMMEs within the Lesotho tourism sector. In addition, a new dimension in respect of adoption was identified, viz. national culture. In this regard, masculinity, type of business ownership, and orientation to online purchasing were found to be mitigating factors against e‐commerce adoption amongst SMMEs in the Lesotho tourism industry. Finally, an adapted UTAUT model is proposed for further study of e‐commerce adoption in a developing country context.